The Pristine Inner Galaxy Survey (PIGS) I: tracing the kinematics of metal-poor stars in the Galactic bulge. (18th October 2019) - Arentsen, A; Starkenburg, E; Martin, N F; Hill, V; Ibata, R; Kunder, A; Schultheis, M; Venn, K A; Zucker, D B; Aguado, D; Carlberg, R; González Hernández, J I; et al.
ABSTRACT: Our Galaxy is known to contain a central boxy/peanut-shaped bulge, yet the importance of a classical, pressure-supported component within the central part of the Milky Way is still being debated. It should be most visible at low metallicity, a regime that has not yet been studied in detail. Using metallicity-sensitive narrow-band photometry, the Pristine Inner Galaxy Survey (PIGS) has collected a large sample of metal-poor ($\rm {[Fe/H]}\, \lt -1.0$ ) stars in the inner Galaxy to address this open question. We use PIGS to trace the metal-poor inner Galaxy kinematics as function of metallicity for the first time. We find that the rotational signal decreases with decreasing [Fe/H] , until it becomes negligible for the most metal-poor stars. Additionally, the velocity dispersion increases with decreasing metallicity for $-3.0 \lt \rm {[Fe/H]}\, \lt -0.5$, with a gradient of −44 ± 4 km s −1  dex −1 . These observations may signal a transition between Galactic components of different metallicities and kinematics, a different mapping on to the boxy/peanut-shaped bulge for former disc stars of different metallicities and/or the secular dynamical and gravitational influence of the bar on the pressure-supported component. Our results provide strong constraints on models that attempt to explain the properties of the inner Galaxy.